2021
DOI: 10.1038/s42003-021-01652-x
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase 4 promotes peritoneal fibrosis and its inhibitions prevent failure of peritoneal dialysis

Abstract: Peritoneal dialysis (PD) possesses multiple advantages for end stage renal disease. However, long-term PD triggers peritoneal fibrosis (PF). From the nationwide analysis of diabetic PD patients (n = 19,828), we identified the incidence of PD failure was significantly lower in diabetic patients treated with dipeptidyl peptidase 4 (DPP4) inhibitors. Experimental study further showed high concentration of glucose remarkably enhanced DPP4 to promote epithelial-mesenchymal transition (EMT) in the mesothelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Immunohistochemical staining protocols were based on our previous study 41 . Briefly, paraffin sections were treated with 3% H 2 O 2 for 10 minutes and incubated with Immuno-Block reagent (BioSB) for 30 minutes at room temperature, followed by incubation with the primary antibody specifically against Ki67 (Abcam) and secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining protocols were based on our previous study 41 . Briefly, paraffin sections were treated with 3% H 2 O 2 for 10 minutes and incubated with Immuno-Block reagent (BioSB) for 30 minutes at room temperature, followed by incubation with the primary antibody specifically against Ki67 (Abcam) and secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of DPP4 was increased in the thickening peritoneum of chlorhexidine gluconateinduced peritoneal fibrosis model of rats. Increased expression of DPP4 in diabetes was found to promote epithelialmesenchymal transition and peritoneal fibrosis, which could be relieved by pharmacological or genetic inactivation of DPP4 (93). Moreover, DPP4 binding to extracellular matrix proteins (such as collagen and fibronectin) and extracellular matrix degrading enzymes (such as plasminogen and streptokinase) probably contributes to cells spreading and metastasis (5,94,95).…”
Section: The Role Of Dpp4 In Fibrosismentioning
confidence: 99%
“…High glucose content induces mesothelial cells to produce transforming growth factor-beta (TGF-β) [ 15 ]. An analysis of 19,828 diabetic patients with PD has demonstrated that exposure to glucose upregulated dipeptidyl peptidase 4 (DPP4) [ 16 ]. The upregulation of dipeptidyl peptidase 4 (DPP4) promoted mesothelial to mesenchymal transition (MMT), which refers to the transition of the mesothelial membranes to the mesenchymal cells.…”
Section: Reviewmentioning
confidence: 99%
“…This clinical observational study of PD patients has shown that DPP4 enzyme played a major role in peritoneal fibrosis and deterioration. Therefore, the use of DPP4 inhibitors can help prevent the MMT [ 16 ] and prevent peritoneal fibrosis as DPP4 inhibition holds antifibrotic effects [ 17 ].…”
Section: Reviewmentioning
confidence: 99%